Overcoming obstacles and maximizing opportunities ([s.n.] [S.l.], 1997)
Recommends ways in which smaller economies can prepare themselves to participate in a hemispheric free trade area, and the mechanisms and measures that could be implemented to facilitate the economic adjustments which must be undertaken as these countries adopt more open trade and investement policies.
Additional copy located in the Office of the Secretary General